The influence of empowerment on collaboration and knowledge sharing and their influence on project success. - S. Wagan; S. Sidra; M. Hoque (Управленческие науки, 2024)
The purpose of this research is to evaluate the effects that empowerment has on the sharing of information and cooperation in an effective project management setting. The purpose of this study is to investigate the direct impacts of empowerment, which will be evaluated based on autonomy and responsibility, on efficiency of cooperation between members of a team, the sharing of information, and the accomplishment of the project. A total of 228 Pakistani project managers were surveyed via the use of questionnaires, and the results were analyzed through the use of SPSS 25.0 and SMART software PLS 4. The findings demonstrated that empowerment has a beneficial impact on the cooperation and information sharing that occurs between team member exchanges and other project teams, which in turn has a favorable influence on the success of the project. While the responsibility of collaborators reflects positively in cooperation and information sharing, the autonomy that is assigned to the exchanges that take place between members of the project team encourages the sharing of knowledge and facilitates the success of the project. Not only do these findings help to the enhancement of theoretical understanding about project management, but they also enhance the practice of project team management. There is an increase in the likelihood of the project being successful as a result of their guidance to project managers on the delegation of autonomy and responsibility to team member exchanges. The research makes a contribution to the cultivation of improved project management techniques and highlights the significance of leadership abilities in the accomplishment of successful project outcomes.